PERANCANGAN ALAT UKUR KETINGGIAN PERMUKAN AIR BERBASIS SENSOR ULTRASONIK MAXSONAR MB7389 DAN MIKROKONTROLER ATMega328P - Elohansen Padang; Baina Afkril; Richard Lewerissa; Jacson Viktor Morin; Mujasam Mujasam (Jurnal Natural, 2022)
In this study, a low-cost water level measurement device based on an ultrasonic sensor was developed. The ultrasonic sensor used is Maxsonar MB7389, and the data acquisition system uses the ATMega328P Microcontroller. Meanwhile, water level measurement data is displayed in real-time on a computer and also stored in a microSD card where data can be retrieved at any time for analysis. The choice of the Maxsonar MB7389 sensor for sensing water levels is based on its superiority in water resistance so that it can be applied in the field, and the measurement resolution is up to millimeters. Meanwhile, the ATMega328P microcontroller contained in the Arduino Uno board has advantages in terms of its relatively low-cost price, ease to program using the open-source Arduino IDE software, supported by many libraries, and modules. Based on the results of laboratory-scale testing, the measurement device developed can measure the water level quite accurately. That can be seen from the average water level measurement error for sensors without a casing of 0.31 cm and sensors with a PVC pipe sheath of 0.25 cm. Then, the value of the Pearson correlation coefficient (R2) is 0.99 for sensors without pipe casings, and 1 for sensors with PVC pipe casings. Then, based on the ripple comparison of the results of the water level measurement, it can be suggested for the measurement of the highly fluctuating water level (such as sea and river) should use a pipe casing. Meanwhile, for measuring the water level in the tank that is not too volatile, you can use a sensor without a pipe casing.